2017
DOI: 10.3390/ph10030067
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Proteome of Rats Subjected to the Li-Pilocarpine Epilepsy Model and the Effect of Carisbamate Treatment

Abstract: In adult rats, the administration of lithium–pilocarpine (LiPilo) reproduces most clinical and neuropathological features of human temporal lobe epilepsy (TLE). Carisbamate (CRS) possesses the property of modifying epileptogenesis in this model. Indeed, about 50% of rats subjected to LiPilo status epilepticus (SE) develop non-convulsive seizures (NCS) instead of motor seizures when treated with CRS. However, the mechanisms underlying these effects remain unknown. The aim of this study was to perform a proteomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
(81 reference statements)
3
12
0
Order By: Relevance
“…Based on previous studies, we can hypothesize that CRS reduces neuronal excitability by acting synergistically on several neurotransmitter systems and pathways. Supporting these data, we recently reported [ 16 ] that CRS-NCS rats display alterations in proteins related to cellular respiration and energy production processes, which may also impact on neuronal excitability. Among altered proteins we observed a reduction of alpha-synuclein in rats treated with CRS and an increase of the same protein in CRS-treated animals displaying NCS instead of convulsive seizures [ 16 ].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Based on previous studies, we can hypothesize that CRS reduces neuronal excitability by acting synergistically on several neurotransmitter systems and pathways. Supporting these data, we recently reported [ 16 ] that CRS-NCS rats display alterations in proteins related to cellular respiration and energy production processes, which may also impact on neuronal excitability. Among altered proteins we observed a reduction of alpha-synuclein in rats treated with CRS and an increase of the same protein in CRS-treated animals displaying NCS instead of convulsive seizures [ 16 ].…”
Section: Introductionsupporting
confidence: 62%
“…Supporting these data, we recently reported [ 16 ] that CRS-NCS rats display alterations in proteins related to cellular respiration and energy production processes, which may also impact on neuronal excitability. Among altered proteins we observed a reduction of alpha-synuclein in rats treated with CRS and an increase of the same protein in CRS-treated animals displaying NCS instead of convulsive seizures [ 16 ]. A recent hypothesis suggests that epigenetic alterations in some proteins such as alpha-synuclein may be associated with the formation of new ion channels that may disrupt membrane conductance and underlie the change in epilepsy type induced by CRS treatment [ 17 ].…”
Section: Introductionsupporting
confidence: 62%
“…Previous studies also reported an up-regulation of DPYSL2 in autopsy and human biopsy tissue from epileptic patients [15]. This protein was also up-regulated in the MTLE model induced by pilocarpine compared to the control, and treatment with a disease modifier neuromodulator, carisbamate, normalized the expression of DPYSL2 [32]. Carisbamate treatment reversed the increase in the protein expression and caused a change in the expression of limbic seizures for absence seizures in treated animals [32].…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have provided important insights into the underlying cellular and molecular processes of epileptogenesis, highlighting neuroinflammation, the innate immune response, microglial activation, synaptic reorganization, and oxidative stress as key mechanisms in this regard (Bitsika et al, ; Keck et al, , ; Li et al, ; Liu et al, ; Marques‐Carneiro et al, ; Walker et al, ). Many of these observations are unsurprising, given the burgeoning knowledge base surrounding the mechanisms and pathways believed to contribute to the development of epilepsy (Aronica et al, ; Becker, ; Godale & Danzer, ; Lukawski et al, ; Pitkänen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the proteomic signature of epileptogenesis to date (Bitsika et al, ; Keck et al, , ; Li et al, ; Liu et al, ; Marques‐Carneiro et al, ; Walker et al, ), all of which have been relatively small scale investigations involving small numbers of animals. In this respect, the current study is no different.…”
Section: Discussionmentioning
confidence: 99%